A pilot feasibility trial of alcohol screening and brief intervention in the police custody setting (ACCEPT): study protocol for a cluster randomised controlled trial. Issue 1 (December 2015) - Birch, Jennifer; Scott, Stephanie; Newbury-Birch, Dorothy; Brennan, Alan; Brown, Heather; Coulton, Simon; Gilvarry, Eilish; Hickman, Matthew; McColl, Elaine; McGovern, Ruth; Muirhead, Colin; Kaner, Eileen
Abstract Background There is evidence of an association between alcohol use and offending behaviour and around a quarter of police time is spent on alcohol-related incidents. Police custody, therefore, provides an important opportunity to intervene. This pilot trial aims to investigate whether a definitive evaluation of screening and brief interventions aimed at reducing risky drinking in arrestees is acceptable and feasible in the custody suite setting. Methods Screening will be carried out by trained detention officers or drug and alcohol workers in four police forces across two geographical areas (North East and South West England). Detention officers (or drug and alcohol workers) will be cluster randomised to one of three conditions: screening only (control group), screening followed immediately by 10 min of manualised brief structured advice delivered by the individual responsible for screening (intervention 1) or screening followed by 10 min of manualised brief structured advice delivered by the individual responsible for screening plus the offer of a subsequent 20-min session of behaviour change counselling delivered by a trained alcohol health worker (intervention 2). Participants will be arrestees aged 18+ who screen positive on the Alcohol Use Disorders Identification Test. Participants will be followed up at 6 and 12 months post-intervention. An embedded qualitative process evaluation will explore acceptability of alcohol screening and brief intervention to staff and arrestees as well as facilitators and barriers to the delivery of such approaches in this setting. Results Recruitment is currently underway and due to end May 2015. Conclusion Results from this pilot trial will determine if a definitive evaluation is possible in the future and will provide stakeholder input to its design. Trial registration Reference number:ISRCTN89291046 .